Fluorescent phenanthroimidazoles functionalized with heterocyclic spacers: synthesis, optical chemosensory ability and two-photon absorption (TPA) properties. (5th October 2017) - Ferreira, Rosa Cristina M.; Costa, Susana P. G.; Gonçalves, Hugo; Belsley, Michael; Raposo, Maria Manuela M.
Abstract : Fluorescent phenanthroimidazoles bearing heterocyclic spacers as novel optical chemosensors and two-photon absorption chromophores. Abstract : Three series of fluorescent phenanthroimidazoles bearing heterocyclic spacers were synthesized in moderate to excellent yields and evaluated as optical chemosensors for ions as well as two-photon absorbing chromophores. Interaction of compounds5–7 with anions and cations in acetonitrile and acetonitrile/H2 O (95 : 5) showed them to be selective receptors for several anions (AcO −, CN − and F − ) and cations (Fe 3+, Cu 2+ and Pd 2+ ), with compound7a being the most sensitive receptor for Fe 3+ and Cu 2+ . On the other hand, compounds5a, 7b and7c were the most sensitive receptors for AcO −, CN − and F − . The binding stoichiometry between the receptors and the anions and cations was found to be 1 : 2 (ligand to anion/metal cation). The binding process was also followed by 1 H NMR titrations. The evaluation of the TPA properties of chosen phenanthroimidazoles7a–c by the two-photon induced fluorescence method revealed that compound7c, which contains a bithienyl spacer, exhibited the highest TPA cross-section ( σ 2 ) value.